Effect of Sodium Thiopental on the Serum Protein Binding of Bupivacaine. Issue 4 (October 1984) - Arthur, Richard G.; Denson, Donald D.; Coyle, Dennis E.
Abstract : The effect of sodium thiopental (6 and 20 μ g/ml) on the protein binding of bupivacaine in human serum was determined at pH values of 7.40 and 7.00. The protein binding of bupivacaine decreased from 96% to 58% as the concentration of this drug in serum was increased from 1 μ g/ml to 100 μ g/ml. A decrease in pH lowered the protein binding of bupivacaine by approximately 2% at 1 μ g/ml and 10% at 100 μ g/ml. Addition of sodium thiopental to human serum did not significantly alter the protein binding of bupivacaine. The results suggest that the use of sodium thiopental to treat convulsive episodes caused by bupivacaine is unlikely to exacerbate the potential cardiovascular toxicity of this agent by increasing the amount of unbound bupivacaine present in blood.